PERTANGGUNGJAWABAN HUKUM PENYELENGGARA PERDAGANGAN MELALUI SISTEM ELEKTRONIK DALAM NEGERI ATAS PEMBIARAN SEPATU SKECHERS PALSU (STUDI KASUS PADA BUKALAPAK) - Rovandie, Rio; Jayakusuma, Zulfikar; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This study aims to find out how the legal accountability of trade operators through the domestic electronic system (PPMSE) for counterfeit goods sold by traders on their platforms based on Government Regulation Number 80 of 2019 concerning Trading Through Electronic Systems (PMSE) and to find out how legal protection is against buyers in PMSE activities based on the laws and regulations in Indonesia. The benefits of this research can increase public understanding of PPMSE's legal responsibilities and about community rights as consumers in PMSE activities. This research can also be input and information material for PPMSE to improve supervision, improvement and security in managing its platform in order to protect its users properly. This type of research is normative legal research. The research approach is a case study on the Bukalapak Platform. The result of the research is that PPMSE can be held legally responsible based on vicarious liability which refers to Article 1367 Paragraph (3) of the Criminal Code if it is proven that due to unlawful acts committed by its workers in processing consumer complaints resulting in consumer losses. The form of legal liability is to compensate consumers who are harmed. The clause in the Bukalapak electronic contract that limits the maximum liability is a violation of the laws and regulations so that the objective conditions of the agreement are not fulfilled and the agreement is null and void. Based on the principle of liability with limitations (limitation of liability) PPMSE can be held legally responsible because the clause is detrimental to consumers. Legal protection for buyers in PMSE activities refers to PP PMSE and UUPK, in these regulations there are various forms of buyer rights that must be protected. obliged to provide compensation, compensation and reimbursement. PPMSE is also obliged to try to protect the rights of buyers, PPMSE is obliged to provide electronic contracts, security systems, complaint services, officers who are competent in processing complaints and assist buyers in resolving problems related to their rights properly. Keywords: Liability – PPMSE – PMSE – Counterfeit – Merchants – Buyers